Unraveling the Impact of Covid-19: Financial Distress and Resilience in Indonesian Retail Giants - I Ketut Mangku; Andika; Nadia; Melli Agustiani (PT Inovasi Pratama Internasional, 2024)
This study aimed to analyze whether PT. Matahari Department Store Tbk, PT. Hero Supermarket Tbk, PT. MAP Active Adiperkasa Tbk, and PT. Erajaya Swasembada Tbk experienced financial distress during the period of 2019-2021. The objective was to identify if any of these companies faced financial difficulties and, if so, determine the main variables that caused their financial problems. A sample of four companies from the Supermarket & Convenience Store, Clothing & Textile Retail, and Electronic Retail sub-industries was chosen using purposive sampling. The data analysis used the Altman Z-score (multiple discriminant analysis) method. The results revealed that two companies, PT. Hero Supermarket Tbk in 2019 and 2020, with Z-scores of 2.9510 and 2.5147, respectively, and PT. Matahari Department Store Tbk in 2020-2021, with Z-scores of 2.1954 and 2.6608, fell within the gray area. The gray area indicates that these companies were at risk of financial distress. Among these two companies, PT. Hero Supermarket Tbk faced financial distress in 2021, as indicated by a Z-score of 0.9288. On the other hand, the analysis indicated that two companies, PT. MAP Active Adiperkasa Tbk and PT. Erajaya Swasembada Tbk, remained in a healthy and safe financial condition throughout the three-year period, as their Z-scores were greater than 2.88. In conclusion, the study highlights the importance of financial health analysis for companies operating in the Supermarket & Convenience Store, Clothing & Textile Retail, and Electronic Retail industries. The Altman Z-score proved to be a valuable tool in identifying financial distress risks and assisting decision-makers and stakeholders in making informed and proactive strategies to mitigate potential financial difficulties.